2022
DOI: 10.1108/cg-11-2021-0418
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between audit committee and corporate risk: evidence from Pakistan

Abstract: Purpose The purpose of this study is to investigate the impact of audit committee (AC) characteristics, such as AC size, AC independence and gender diversity on firm risk in the context of an emerging market. Design/methodology/approach The sample data includes 102 nonfinancial Pakistan Stock Exchange listed firms from 2004 to 2018. Firm risk is measured through three proxies, namely, idiosyncratic risk, total risk and capital expenditure. Along with this, profitability, leverage, market-to-book ratio, firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 78 publications
2
8
0
Order By: Relevance
“…Feng et al (2021) find a higher market valuation of cash holding for firms evaluated by industry authority examiners. Similar findings are supported by Noor et al (2022) and Ullah et al (2019). Gong et al (2019) found that industry pro auditor decreases power and snugness of obligation.…”
Section: Introductionsupporting
confidence: 74%
“…Feng et al (2021) find a higher market valuation of cash holding for firms evaluated by industry authority examiners. Similar findings are supported by Noor et al (2022) and Ullah et al (2019). Gong et al (2019) found that industry pro auditor decreases power and snugness of obligation.…”
Section: Introductionsupporting
confidence: 74%
“…(2016), who suggest that gender diversity in the subcommittees may also be a formality. In addition, Noor et al. (2022) contend that minimal representation of women, especially in subcommittees, makes gender diversity insignificant or even negative relevant to disclosure.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there have been banks that have had more than one female member on the overall board. Therefore, the explanations of Noor et al. (2022) and Chijoke-Mgbame et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All models are subjected to multiple regression analysis using the fixed-effect method, which was chosen based on the panel data model selection test (Gujarati and Porter, 2009;Wooldridge, 2016). The fixed-effect method yields the most efficient estimation, as shown in the results in Appendix 2 (Gujarati and Porter, 2009;Arora and Sharma, 2016;Wooldridge, 2016;Mayur and Saravanan, 2017;Santos et al, 2019;Barros et al, 2020;Tahir et al, 2020;Tran, 2021;Khursheed and Sheikh, 2022;Noor et al, 2022). In addition, we also applied a robust standard error to all the models (Koester et al, 2016) and to all the regression analyses because there were pieces of evidence that the residual of the models suffered from non-normality, heteroscedasticity and autocorrelation (in Appendices 3 and 4).…”
Section: Discussionmentioning
confidence: 99%